Market Share as a Firm Driver: Important Strategic Implications from Reviewing Literature from 1974-1995 - Almurshidee, Khalid A. (Business Management and Strategy, 2024)
The important strategic implications of market share were and still needed to be clearly understood. In particular, the relationship between market share and profitability have not been settled in business literature until the mid-ninety of last century. Researchers were able clarify this relationship mainly because of The possibilities it provided by PIMS data. This paper reviews the main literature on the different aspects and concepts of market share and its strategic implications from 1974-1995; the period in which this topic was in its peak; which is in return has yielded the most important academic thoughts and inferences to the subject of strategic planning. The most notable one is with regard to the conclusion that market share caused profitability has been proven to be overly simplistic.